Empowering Hospitals to Thrive: Integrating Health Informatics, Medical Secretaries, Health services and hospital management to Mitigate Staffing Shortages - Hamad Mana Mohammed Alsalem, Feheid Moslat Alsubei, Mohammed Sami Ibrehim Alhushum, Rowaida Salamh Al-Rehaliy, Hamad Salem Hassan Al Salem, Ghayah Mohammed Al-Madawisi, Abrar Mubarak Saeed Alnaseeb, Hanaa Saeed Aseeri (Journal of International Crisis and Risk Communication Research, 2024)
Inadequate staffing in hospitals is a critical challenge that significantly affects patient care, staff well-being, and overall hospital efficiency. This review focuses on the integration of health informatics, medical secretaries, health services, and hospital management as key strategies to mitigate inadequate staffing. Health informatics optimizes resource allocation through data-driven decisions, enhancing workforce efficiency and training. Medical secretaries support hospital operations by managing patient records, communication, and administrative tasks, which alleviate the workload on clinical staff. Health services contribute by implementing innovative recruitment and retention strategies, while hospital management plays a pivotal role in improving work environments and optimizing staffing policies. The review explores how these integrated approaches can create a more resilient healthcare system and ensure adequate staffing levels for improved patient outcomes and quality of care.